Distribution of laminins in the basement membranes of the upper gastrointestinal tract and Barrett's oesophagus - Dave, U; Thursz, MR; Ebrahim, HY; Burke, MM; Townsend, ER; Walker, MM (The Journal of pathology, 2004)
Barrett's oesophagus predisposes to oesophageal adenocarcinoma. In vitro, laminin, a component of the epithelial basement membrane (BM), is important in regulation of cell differentiation. There is limited information on the distribution of laminin chains in the upper gastrointestinal tract (GIT) and none in Barrett's oesophagus. This study aimed to investigate qualitatively the distribution of laminins in the normal upper GIT mucosa and Barrett's oesophagus in order to understand the role of laminins in metaplasia. Immunoperoxidase staining for laminin chains α1, α2, α3, α5, β1, β2, β3, γ1, and γ2 was performed on frozen endoscopic squamous and Barrett's oesophageal biopsies and surgical resection specimens from squamous oesophagus (in resection specimens for oesophageal cancer), and in oesophageal and gastric biopsies from control subjects. α1 laminin was expressed in the BM of submucosal glands and ducts in squamous oesophagus and Brunner's glands in the duodenum, but not in Barrett's oesophagus or elsewhere in the upper GIT. α2 laminin chain was expressed in a granular distribution in the BM of squamous epithelium. In columnar epithelium, including Barrett's oesophagus, α2 laminin chain was expressed continuously in the BM of glands and deeper pits, but expression was reduced and granular in the surface epithelial BM. β2 laminin was continuous in squamous epithelial BM, but in Barrett's and cardia, gastric body, and duodenum, it was expressed faintly in the surface but continuously in the BM of glands and deeper pits. The constituents of laminin‐5 were continuously expressed in the BM of squamous epithelium, but in the cardia, gastric body, duodenum, and Barrett's, they were expressed only in the BM of surface epithelium, with a sharp decline in the glandular and deeper pit BM. Site‐specific distribution of the α2 and β2 laminin chains may therefore have an important role in Barrett's metaplasia. However, the absence of α1 laminin in Barrett's mucosa suggests that this is unlikely to play an important role in columnar metaplasia. Copyright © 2004 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.